Strategi Guru Dalam Penerapan Pembelajaran Berdiferensiasi Pada Mata Pelajaran Bahasa Inggris Di SDI Mutiara Islam Al-Ittiba’ - Ningsih, Widia; Setyani, Viera; Belawati Pandiangan, Anjani Putri (EDUCATE : Journal of Education and Culture, 2024)
This research aims to determine the strategies in differentiated learning carried out by English teachers in learning activities at SDI Mutiara Islam Al-Ittiba The method used by researchers in this study uses a qualitative approach, which uses interview techniques with sources to obtain accurate information. Differentiated learning is learning that adapts students' interests and talents to achieve good learning outcomes. Of course, this can be realized by using appropriate strategies that suit students' different learning styles. Therefore, teachers must support their students so they can achieve their learning goals. Based on the research results, it can be concluded that differentiated learning can significantly improve student learning outcomes by using appropriate strategies that suit students' learning styles to obtain maximum results.